Construção de metodologia para avaliação do uso de informação geográfica na gestão pública municipal - Almeida, Vitor Laytynher Santos de (Universidade Federal de São Carlos, 2023)
In an urban context, many technological advances in areas such as remote sensing, computation, and information technology have enabled the gathering of a massive quantity of geographic data, which contributes to the decision making of governments. These are data about traffic and vehicles, about infrastructure network, socioeconomic data, territory demarcations, and many other types of data from different sectors, which need to become compatible, to be organized, and to be easily accessed in order to benefit public policies. In Brazil, although there are institutional incentives to the efficient managing of geographic information, many city level administrations still have a hard time dealing with this type of data. The goal of this project is to create and test a method able to quantify the use of geographic information in city hall processes and decisions, named GeoPerformance City Test. In order to do that, it was stablished some indicators (use patterns, data&software, operators, regulations, external use) and some parameters that would assemble a complete picture of the geographical data and its application context regarding a municipality. These indicators were then calibrated through consultation of specialized personnel following Delphi process. After that, it took place the geographic data conditions assessment for voluntary cities. As a result, specialized personnel pointed Data&Software and Operators as the most important items in order to seize full geographic data potential. However, city halls that contributed with the research pointed the lack of specialization on the matter, and also a generalized deficiency in institutional websites offering geographic data. Besides, there wasn't a strong agreement among consultants regarding indicators and parameters weights, as these factors showed substantial variations along the process. Main conclusion is that it seems to exist an impediment to the offering of city geoportals for common users, although city halls recognize spatial data as an important asset, hence the good results in Data&Software. Yet, there are still weak points, such as instructions and standards, and operators specialization. Regarding the assessment methodology, it showed that the gathering of information happens fast among cities, maybe due to the answer-guided form, and that it provides a fast and wide-ranging diagnosis about spatial data situation in city hall.
Creation of method to evaluate geographic information use in city hall administration
Keywords: Sistema de informação geográfica; Dados espaciais; Administração Pública Municipal; Prefeituras; Spatial data; Public Administration; Geographic information system; City hall; ENGENHARIAS